2019
DOI: 10.3390/molecules24050952
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of pH Using an i-Motif-Forming Sequence Containing a Fluorescent Cytosine Analogue, tC

Abstract: The i-motif is a four-stranded DNA structure formed from the cytosine (C)-rich ssDNA sequence, which is stabilized in slightly acidic pH. Additionally, labeling of a cytosine-rich sequence with a fluorescent molecule may constitute a way to construct a pH-sensitive biosensor. In this paper, we report tC-modified fluorescent probes that contain RET-related sequence C4GC4GC4GC4A. Results of the UV absorption melting experiments, circular dichroism (CD) spectra, and steady-state fluorescence measurements of tC-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Previously, we have indicated that emission of molecular beacon containing tC analogue incorporated in cytosine-rich loop underwent gradual quenching upon changing pH from 8.0 to 5.5 15 . This efficiently quenched fluorescence of tC was ascribed to the protonated tC-H + fluorophore that was generated upon i-motif formation 48,51 . Thus, we expected that tC-MB-520 fluorescence signal would rather decrease upon pH lowering instead of increasing as shown in Fig.…”
Section: (Insert)mentioning
confidence: 99%
“…Previously, we have indicated that emission of molecular beacon containing tC analogue incorporated in cytosine-rich loop underwent gradual quenching upon changing pH from 8.0 to 5.5 15 . This efficiently quenched fluorescence of tC was ascribed to the protonated tC-H + fluorophore that was generated upon i-motif formation 48,51 . Thus, we expected that tC-MB-520 fluorescence signal would rather decrease upon pH lowering instead of increasing as shown in Fig.…”
Section: (Insert)mentioning
confidence: 99%
“…The DNA template used for the synthesis of silver nanoclusters (AgNCs) was cytosine-rich (Crich) oligonucleotide related to the RET sequence: 5′-CCCCGCCCCGCCCCGCCCCA-3′ (RET20) [18]. In this work, we also report fluorescent AgNCs synthesized on tC-modified oligonucleotides that contain the same RET-related sequence: 5′-CCCCGCCCCGCCCCGCCCtCA-3′ (RET19tC) and 5′-CCCCGCCCCGCCCtCGCCCCA-3′ (RET14tC) [20]. 1,3-diaz-2-oxophenoxazine, tC is a tricyclic cytosine analog, which is a highly fluorescent marker with an absorption maximum at 385 nm and an emission maximum at 500 nm [21].…”
Section: Resultsmentioning
confidence: 96%
“…In the presented work, we compare the absorption and emission properties of the obtained systems with silver nanoclusters synthesized on the unmodified oligonucleotide with the RET-related sequence. The oligonucleotides of choice are able to form four-stranded DNA structures called imotifs [18][19][20]. The implications coming from fact using the folded i-motif structure as a template for the synthesis of silver nanoclusters will be also presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…UV‐Vis and circular dichroism (CD) spectroscopy have also been applied in studies of the hTel iM structure [1a] . Fluorescence spectroscopy has been the most widely used technique for investigating the conformational changes of iM structures because of its low cost and high sensitivity [5–8] …”
Section: Figurementioning
confidence: 99%
“…Fluorescent nucleobases have often been used to modify iM DNA sequences, allowing tracking of, for example, their fluorescence, [5] excimer emission, [6] anisotropy, [7] and photoinduced electron transfer [8] . In most examples of iM structures containing these fluorescent nucleobases, variation of the pH has not led to an increase in fluorescence intensity, but rather a quenching of the emission.…”
Section: Figurementioning
confidence: 99%